Non-coding transcription SETs up regulation - Venkatesh, Swaminathan (Nature Publishing Group, 2013)
An abundance of long non-coding RNA (lncRNA) present in most species from yeast to human are involved in transcriptional regulation, dosage compensation and imprinting. This underscores the importance of lncRNA as functional RNA despite the fact that they do not produce proteins. Two recent papers in Cell have demonstrated that transcription of the non-conserved lncRNAs, but not the RNAs themselves, is necessary to introduce co-transcriptional regulatory histone marks to regulate gene expression.